2018
DOI: 10.3390/ijms19041106
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Atorvastatin Applied Acutely after Spinal Cord Injury Suppresses Inflammation, Apoptosis, and Promotes Axon Outgrowth, Which Might Be Essential for Favorable Functional Outcome

Abstract: The aim of our study was to limit the inflammatory response after a spinal cord injury (SCI) using Atorvastatin (ATR), a potent inhibitor of cholesterol biosynthesis. Adult Wistar rats were divided into five experimental groups: one control group, two Th9 compression (40 g/15 min) groups, and two Th9 compression + ATR (5 mg/kg, i.p.) groups. The animals survived one day and six weeks. ATR applied in a single dose immediately post-SCI strongly reduced IL-1β release at 4 and 24 h and considerably reduced the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 49 publications
(60 reference statements)
0
40
0
Order By: Relevance
“…Atorvastatin, lovastatin, pravastatin, and simvastatin, drugs competitively inhibiting HMG-CoA (3-hydroxymethylglutaryl-coenzyme A) reductase, are widely used in the treatment of dyslipidaemias and prevention of atherosclerotic cardiovascular complications. They are also able to support neuronal survival and improve functional recovery after SCI (Bimbova et al 2018). The positive influence of statins on neuronal survival and restriction of TM size is mediated by activation of the Wtn/β-catenin signalling pathway, reduction of levels of inflammatory factors (such as TNF-α, and IL-1β), infiltration of SC by destructive M 1 macrophages, restriction of endothelial nitric oxide, and by inhibition of caspase-3 and caspase-9 cleavage in SC neurons, astrocytes, and oligodendrocytes (Bimbova et al 2018).…”
Section: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atorvastatin, lovastatin, pravastatin, and simvastatin, drugs competitively inhibiting HMG-CoA (3-hydroxymethylglutaryl-coenzyme A) reductase, are widely used in the treatment of dyslipidaemias and prevention of atherosclerotic cardiovascular complications. They are also able to support neuronal survival and improve functional recovery after SCI (Bimbova et al 2018). The positive influence of statins on neuronal survival and restriction of TM size is mediated by activation of the Wtn/β-catenin signalling pathway, reduction of levels of inflammatory factors (such as TNF-α, and IL-1β), infiltration of SC by destructive M 1 macrophages, restriction of endothelial nitric oxide, and by inhibition of caspase-3 and caspase-9 cleavage in SC neurons, astrocytes, and oligodendrocytes (Bimbova et al 2018).…”
Section: Statinsmentioning
confidence: 99%
“…They are also able to support neuronal survival and improve functional recovery after SCI (Bimbova et al 2018). The positive influence of statins on neuronal survival and restriction of TM size is mediated by activation of the Wtn/β-catenin signalling pathway, reduction of levels of inflammatory factors (such as TNF-α, and IL-1β), infiltration of SC by destructive M 1 macrophages, restriction of endothelial nitric oxide, and by inhibition of caspase-3 and caspase-9 cleavage in SC neurons, astrocytes, and oligodendrocytes (Bimbova et al 2018). Although a long-term statin therapy can cause myopathy which may progress to rhabdomyolysis, new-onset type-2 diabetes mellitus and, probably, haemorragic stroke, the less serious adverse effects of statin therapy generally resolve rapidly when administration is terminated (Peto and Collins 2018).…”
Section: Statinsmentioning
confidence: 99%
“…1,2 Neuronal apoptosis is an important component of secondary SCI and spinal nerve cell death after SCI is caused by apoptosis. [3][4][5] Studies in different SCI models have confirmed that neuronal apoptosis is widespread in secondary SCI. 6,7 Apoptosis, also known as programmed cell death, is an intrinsic natural physiological process that maintains the stability of various tissues in the human body by eliminating metabolites of dead cells.…”
Section: Introductionmentioning
confidence: 95%
“…Spinal cord injury (SCI) is a serious threat to human health, which includes primary and secondary injuries . Neuronal apoptosis is an important component of secondary SCI and spinal nerve cell death after SCI is caused by apoptosis . Studies in different SCI models have confirmed that neuronal apoptosis is widespread in secondary SCI .…”
Section: Introductionmentioning
confidence: 99%
“…Among the drugs used for other pathologies, atorvastatin (ATR)—a potent inhibitor of cholesterol biosynthesis—can modulate secondary injury, reducing Interleukin 1 (IL1), M1 macrophage infiltration, and decreasing the activity of caspase 3. These changes lead to increased sprouting and improved locomotor activity [ 5 ]. Pharmacological treatment can be combined with stem cells, but these therapies do not always have to synergize, as in the case of ependymal stem/progenitor cells combined with a pharmacological compound FM19G11, which reduced glial scar and increased the expression of Olig1 in vivo, but did not lead to greater behavioral improvement when compared with the individual treatments [ 6 ].…”
mentioning
confidence: 99%